Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.bja.2018.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic arterial elastance measured by uncalibrated pulse contour analysis predicts arterial-pressure response to a decrease in norepinephrine

Abstract: DRCIT95.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…The sample size also limited the use of parametric approach and prevented the realisation of more specific analysis such as ROC curve comparison between TTE-E Adyn and PCA-E Adyn (or TTE-SVV and PCA-SVV). The monocentric nature of the study limits the external validity, but our results are in accordance with previously reported data [7][8][9] . Finally, we did not measure ventriculo-arterial coupling.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The sample size also limited the use of parametric approach and prevented the realisation of more specific analysis such as ROC curve comparison between TTE-E Adyn and PCA-E Adyn (or TTE-SVV and PCA-SVV). The monocentric nature of the study limits the external validity, but our results are in accordance with previously reported data [7][8][9] . Finally, we did not measure ventriculo-arterial coupling.…”
Section: Discussionsupporting
confidence: 91%
“…Dynamic elastance (E Adyn ) might be estimated as the ratio of stroke volume variation (SVV) to pulse pressure variation (PPV). Authors have demonstrated that E Adyn measured by calibrated pulse contour analysis (PCA-E Adyn ) and by uncalibrated pulse contour analysis can predict the pressure response to a decrease in norepinephrine [7][8][9] . Patients with acute circulatory failure and treated with vasopressors are not always monitored by calibrated pulse contour analysis.…”
Section: Rocmentioning
confidence: 99%
See 1 more Smart Citation
“…One can suppose that in patients treated with vasopressor, Ea dyn mainly reflects vascular resistance because C A is fixed. This hypothesis may also explain the ability of Ea dyn (when measured with an uncalibrated CO device) to predict arterial pressure changes (Bar et al, 2018b). The arterial load and Ea dyn may vary in a complex manner as a function of the therapeutic intervention while decreasing Ea dyn 's ability to predict blood pressure changes.…”
Section: Discussionmentioning
confidence: 99%
“…In preload-dependent patients,[41] it may predict whether blood pressure will increase along with cardiac output following fluid administration, or it may predict whether vasopressors may be reduced whilst maintaining blood pressure. [3942] As such, it may guide in functionally assessing afterload and may discriminate between hypotension secondary to either hypovolaemia (Ea dyn high, fluids probably beneficial), or hypovolaemia secondary to vasoplegia (Ea dyn low), requiring vasopressor(s). Figuratively, we might consider Ea dyn the SVV of the pressure world.…”
Section: Hpi and The Cause Of Hypotensionmentioning
confidence: 99%